Penggunaan Visi Komputer untuk Mengidentifiksi Jenis Buah dari Gambar - Supiyandi Supiyandi; Rafif Rasendriya (Router : Jurnal Teknik Informatika dan Terapan, 2024)
Computer vision technology has advanced rapidly and made significant contributions across various fields, including object identification in images. This study aims to develop a computer vision-based system to identify fruit types from images. A machine learning model is applied using a dataset of fruit images to train the system for accurate fruit recognition. The primary processes include data acquisition, image preprocessing, feature extraction, model training, and performance evaluation. The results demonstrate a high level of accuracy in identifying specific fruit types, showcasing the potential of this technology in agricultural and commercial applications.